An economic evaluation of tranexamic acid to prevent postpartum haemorrhage in women with vaginal delivery: the randomised controlled TRAAP trial. (2nd September 2020) - Durand‐Zaleski, I; Deneux‐Tharaux, C; Seco, A; Malki, M; Frenkiel, J; Sentilhes, L
Abstract : Objective: To estimate the cost‐effectiveness of tranexamic acid (TXA) use to prevent postpartum haemorrhage. Design: A trial‐based economic evaluation. Setting: Fifteen French university maternity hospitals. Population: Women enrolled in the TRAAP randomised controlled trial comparing TXA versus placebo in women with vaginal delivery. TRAAP failed to show a reduction in postpartum haemorrhage of at least 500 ml in the intervention arm but evidenced significant lower rates of secondary outcomes related to blood loss. Methods & main outcome measures: We estimated direct medical costs from within‐trial hospital resources collected prospectively from the study report form. All resources were costed at their value to the hospital. We estimated incremental cost per incremental haemorrhage averted. Results: Among the 4079 women in the TRAAP trial, data necessary to calculate costs were available for 3836 (94.0%). The average total costs in the TXA and control groups were € 2278 ± 388 and €2288 ± 409 per woman, respectively ( P  = 0.79). In women with postpartum haemorrhage of at least 500 ml (trial primary endpoint), costs were €2359 ± 354 and €2409 ± 525 ( P  = 0.14); for provider‐assessed clinically significant postpartum haemorrhage and postpartum haemorrhage of at least 1000 ml, costs were respectively €2316 ± 347 versus €2381 ± 521 ( P  = 0.22) and €2321 ± 318 versus €2411 ± 590 ( P  = 0.35) in the tranexamic and placebo groups, respectively. The probabilistic sensitivity analysis showed that the use of TXA had a 65–73% probability of saving costs and improving outcome. Conclusions: Our findings support the use of TXA, as both bleeding events and cost may be reduced three out of four times. Tweetable abstract: Tranexamic acid at vaginal delivery reduces both costs and bleeding events 3 times out of 4. Tweetable Abstract: Tranexamic acid at vaginal delivery reduces both costs and bleeding events 3 times out of 4.